2010
DOI: 10.1111/j.1095-8312.2010.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity and limitations of extended egg retention in oviparous Zootoca vivipara (Reptilia: Lacertidae)

Abstract: The transition between oviparity and viviparity in reptiles is generally accepted to be a gradual process, the result of selection for increasingly prolonged egg retention within the oviduct. We examined egg retention plasticity in an oviparous strain of the lacertid lizard Zootoca vivipara, a species having both oviparous and viviparous populations. We forced a group of female Z. vivipara to retain their clutch in utero by keeping them in dry substrata, and assessed the effect on embryonic development and hat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Most experimental studies on embryological development have relied on constant temperature experimental treatments with limited understanding on the effect of time available for maternal thermoregulation on embryo development that may have a strong impact on viviparity (Foucart et al., 2018). Our approach on the species of the L. darwinii group provided strong support for the maternal manipulation hypothesis as viviparous pregnant females showed a significantly lower CV than ovigerous females of oviparous species, as observed in other studies (Ji et al., 2007; Rodríguez‐Diaz & Braña, 2011; Schwarzkopf & Andrews, 2012; Wang et al., 2017). Preferred temperature (Hare et al., 2009; Qualls & Andrews, 1999) showed no significant differences between these reproductive modes in Liolaemus , providing little support for the cold climate hypothesis in this experiment.…”
Section: Discussionsupporting
confidence: 85%
“…Most experimental studies on embryological development have relied on constant temperature experimental treatments with limited understanding on the effect of time available for maternal thermoregulation on embryo development that may have a strong impact on viviparity (Foucart et al., 2018). Our approach on the species of the L. darwinii group provided strong support for the maternal manipulation hypothesis as viviparous pregnant females showed a significantly lower CV than ovigerous females of oviparous species, as observed in other studies (Ji et al., 2007; Rodríguez‐Diaz & Braña, 2011; Schwarzkopf & Andrews, 2012; Wang et al., 2017). Preferred temperature (Hare et al., 2009; Qualls & Andrews, 1999) showed no significant differences between these reproductive modes in Liolaemus , providing little support for the cold climate hypothesis in this experiment.…”
Section: Discussionsupporting
confidence: 85%
“…Subsequent research rejected that view, but recent experimental studies have confirmed that exposure to dry conditions or low temperatures can induce females to retain their eggs in utero for longer than usual (Stamps, 1976;Telemeco, Radder, Baird, & Shine, 2010;Warner & Andrews, 2003). Nonetheless, such prolongation typically has little effect on subsequent incubation periods (Mathies & Andrews, 1999;Rodriguez-Diaz & Brana, 2010;Shanbhag, Saidapur, & Radder, 2003;Telemeco et al, 2010;Warner & Andrews, 2003). In Sceloporus aeneus and S. scalaris, however, oviductally retained embryos continue to develop in utero, reducing the subsequent incubation period (Andrews & Mathies, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our results indicate that although the energetic demands of regeneration seem to constrain reproductive investment in P. muralis , they do not affect the incubation time. This probably indicates that there were no differences between intact and regenerating females in the retention time and the level of development reached by the embryos at the time of egg laying, although this trait may have a certain plasticity in lacertid lizards (Braña et al., 1991; Rodríguez‐Díaz & Braña, 2011). Previous studies showed that oviposition in female wall lizards occurs when embryos reached stages 25–29, according to the Dufaure and Hubert (1961) development table (Braña et al., 1991), and that the incubation time at 29°C ranges from 33 to 35 days and is not affected by egg mass (Ji & Braña, 1999), which is in accordance with our results.…”
Section: Discussionmentioning
confidence: 99%